Investigation of Stretch and Recovery Property of Weft Knitted Regular Rib Fabric - Tamanna, Taslima Ahmed; Shibly, Mohammad Abul Hasan; Nurunnabi; Suruj-Zaman, Md.; Mondal, Bivuti Vusan; Saha, Palash Kumar (European Scientific Journal, ESJ, 2017)
Weft knitted regular rib (1×1) fabric stretch and recovery property are very tough to control. This project and thesis work have been devoted to studying the effect of variation of stitch length, yarn count, and GSM on the stretch and recovery properties of weft knit regular rib fabric. Three yarn counts, each with 4 level of stitch length, was manufactured for the purpose of this experiment, remaining the machine set up, dyeing and finishing process constant. In this research, it was found that the better stretch and recovery property of regular rib fabric can be produced by using 2.6 mm to 2.65 mm stitch length for yarn count of Ne 28/1 KH and GSM of 195 to 205.